Burkholderia contaminans: a potential soil-borne antagonist against Rhizoctonia solani causing black scurf and stem canker in potato (Annals of Bangladesh Agriculture, 2025)
Antagonistic bacteria provide a greener alternative to synthetic fertilizer that also promote the plant growth in addition to preventing soil-borne fungus. In the present study, 10 bacterial isolates were isolated from the stem or leave and tuber of the potato from the research field of Gazipur Agricultural University (GAU), Gazipur, Bangladesh. The in vitro dual culture assay confirmed the antagonism of three isolated bacteria against potato black scurf and stem canker fungi Rhizoctonia solani. The selected antagonistic bacteria were characterized with different biochemical tests. The bacterial strains were Gram negative rods. Positive results in protease activity, potassium solubilization, phosphate solubilization, starch solubilization, and urease tests signified their potentiality as contributors to solubilize protein, potassium, phosphorus, starch, and ammonium in soil. The positive result during indole acetic acid (IAA) test indicated the growth promotion activities of the three isolates. Molecular data identified the bacterial strains B2 (MZ396406), B3 (MZ396407), and B4 (MZ396408) as Burkholderia contaminans. Among the three strains, B4 (MZ396408) significantly improved plant growth, suppressed the specific disease symptom, and increased potato yield during field and pot trials. The maximum plant height (29.75 cm), branching (4.73), leaf number per plant (57.3), yield (999.67 g/5p) was recorded in the B4 (MZ396408) treated plot in the field experiment. Whereas, minimum plant height (16.00 cm), branching (3.2), leaf number per plant (31.23), yield (523.00 g/5p) was recorded in negative control in the field experiment. The highest severity of stem canker (65%), black scurf (30%) and presence of sclerotia percentage (80%) was recorded in R. solani inoculated plot, whereas the lowest (0%) stem canker, black scurf and presence of sclerotia were found in the treatment B4 (MZ396408) treated plot. This strain can be used as reference strain for further study.Ann. Bangladesh Agric. 29(1): 23-50